Je Ne Sais Pas, Il Faut Croire: Upaya Memahami Epistemologi Ketuhanan Menurut Jacques Derrida - Kristianto, Andreas (Marturia, 2021)
AbstractOften religion becomes a text of terror / violence which becomes the norm of absolute truth, while 'others' becomes a marginal subject and is outside the truth. Derrida actually criticizes through decontrucsive reading of the presence of religion which is often absolute (logocentrism) in its hegemonic character towards the others (the other). Derrida developed a deconstruction effort which pointed to the impossibility itself, namely the impossibility of talking about God or talking about God. In this paper, Derrida's idea of a God who is a Mysterious Magnum in a jungle of endless trails is described. Apocalyptic and apophatic theology ideas in 'The Impossible' about the Other. At the end, I will reflect theologically about believing in the impossibility of an alternative effort to live in a plurality of religions. AbstrakSeringkali agama menjadi teks teror/ kekerasan yang menjadi norma kebenaran mutlak, sedangkan ‘yang lain’ menjadi subjek marjinal dan ada di luar kebenaran. Derrida justru melakukan kritik melalui pembacaan yang bersifat dekonstrukstif terhadap kehadiran agama yang seringkali bersifat absolut (logosentrisme) wataknya yang hegemoni terhadap the others (sang liyan). Derrida mengembangkan upaya dekonstruksi yang menunjuk pada ketidakmungkinan itu sendiri yaitu ketidakmungkinan untuk membicarakan Tuhan atau berbicara tentang Tuhan. Dalam tulisan ini, diuraikan gagasan Derrida tentang Tuhan yang Magnum Misterium dalam rimba jejak yang tiada ujung. Gagasan teologi apokaliptik dan apofatik dalam ‘Yang Tak Mungkin’ tentang the Other. Pada bagian akhir, saya akan merefleksikan secara teologis tentang beriman dalam ketidakmungkinan sebagai upaya alternatif hidup dalam pluralitas agama.